Punishment of Stealing from Public Money: A Contrastive Jurisdical Study - Abdulrazzaq Ali, Enas (International Journal of Psychosocial Rehabilitation, 2020)
In the Name of Allah, the Most Beneficent, the Most Merciful. All the praises and thanks be to Allah Who Provides mankind with all the necessities of a decent life, the most important of which is the preservation of money. The Islamic Sharia has been keen to promote a decent life and a secure life for every human being, by protecting the interests of Muslims through eliminating corruption and everything that would destroy society. The thieves who covertly terrorize and terrify people and plunder their money secretly, pose a great threat to society, its security, and its safety and therefore should receive a punishment for this crime in proportion to their act, and the purpose of the punishment is reform and restraint, and to preserve society’s security and stability so that one lives safe and feels at ease about his money. Allah Almighty says in the Holy Qur’an: “And as for the man who steals and the woman who steals, cut off their hands in retribution of their offence as an exemplary punishment from Allah. And Allah is Mighty, Wise. It is Allah’s Wisdom and Mercy on His worshipers to impose the punishment for cutting off the thief's hand, and cutting is the appropriate rule to reward the thief without imperfection and inequity. That is why Islamic Sharia does not make his punishment caning, as it is not that deterrent punishment for the crime, and does not make it murder as it is severe ruling, so cutting the hands of thieves was the most appropriate punishment. This ruling was a necessity of His Wisdom, Mercy, and Justice for His worshipers. The theft is forbidden for the thief as it is from Bayt al-mal “House of Muslims’ Wealth” which is the treasury of the state, that is, the place where the public funds of the state are saved and the theft is also a treachery of every Muslim. The theft here is unlike stealing a specific person, from who you can absolve. In our time, such a kind of theft happened when money from Bayt al-mal “House of Muslims’ Wealth” was looted after the US-led occupation of Baghdad, where a group of laymen robbed the state’s institutions, and plundered them; nevertheless, we did not hear any of our esteemed scholars agreeing that this act is permitted. All Muslim scholars and philologists agree that whoever assault Muslims’ Wealth - the state’s properties and banks - by damaging and stealing should guarantee returning what was destroyed or stolen, and that whoever took something of the state’s property should return a similar one like the stolen, with its value if it was valuable. The dispute among Muslim scholars and philologists was about cutting off the thief's hand, and they have two interpretations on this ruling and this is what we are trying to shed light on in the study entitled research: “Punishment of Stealing from Public Money: A Contrastive Jurisdical Study”.Praise be to Allah, Lord of the Worlds, and prays and peace be upon our master Muhammad and his family and companions.